Mechanisms and factors associated with tackle-related injuries in South African youth Rugby Union players - Burger, N.; Lambert, M. I.; Viljoen, W.; Brown, J. C.; Readhead, C.; den Hollander, S.; Hendricks, S. (The American Journal of Sports Medicine, 2017)
Background: The majority of injuries in rugby union occur during tackle events. The mechanisms and causes of these injuries are well established in senior rugby union. Purpose: To use information from an injury database and assess video footage of tackle-related injuries in youth rugby union matches to identify environmental factors and mechanisms that are potentially confounding to these injuries. Study Design: Descriptive epidemiological study. Methods: Injury surveillance was conducted at the under-18 Craven Week rugby tournament. Tackle-related injury information was used to identify injury events in match video footage (role-matched noninjury tackle events were identified for the cohort of injured players). Events were coded using match situational variables (precontact, contact, and postcontact). Relative risk ratio (RRR; ratio of probability of an injury or noninjury outcome occurring when a characteristic was observed) was reported by use of logistic regression. Results: In comparison with the first quarter, injury risk was greater in the third (RRR = 9.75 [95% CI, 1.71-55.64]; P = .010) and fourth quarters (RRR = 6.97 [95% CI, 1.09-44.57]; P = .040) for ball carriers and in the fourth quarter (RRR = 9.63 [95% CI, 1.94-47.79]; P = .006) for tacklers. Ball carriers were less likely to be injured when they were aware of impending contact (RRR = 0.14 [95% CI, 0.03-0.66]; P = .012) or when they executed a moderate fend (hand-off) (RRR = 0.22 [95% CI, 0.06-0.84]; P = .026). Tacklers were less likely to be injured when performing shoulder tackles (same side as leading leg) in comparison to an arm-only tackle (RRR = 0.02 [95% CI, 0.001-0.79]; P = .037). Ball carriers (RRR = 0.09 [95% CI, 0.01-0.89]; P = .040) and tacklers (RRR = 0.02 [95% CI, 0.001-0.32]; P =.006) were less likely to be injured when initial contact was made with the tackler`s shoulder/arm instead of his head/neck. Conclusion: The relative risk of tackle-related injury was higher toward the end of matches. Incorrect technique may contribute to increased injury risk. Implementing recovery strategies between matches, training safe and effective techniques, and improving levels of conditioning may counter the negative effects of fatigue. These findings may assist stakeholders in youth rugby to formulate injury prevention strategies and may improve the preparation of field-side medical staff for managing tackle-related injuries at these or similar tournaments.